Analysis of Protein and Calcium Content in White Swallow’s Nest Stew (Collacalia Fuchiphaga) - Lilla Puji Lestari; Rio Arisandi Pratama (Universitas Muhammadiyah Sidoarjo, 2021)
Swallow's nest (Collocalia fuchiphaga) is one of the high export commodities. This is because the bird's nest is considered to be nutritious in terms of health. In this research, using swallow's nest obtained from several swallow buildings in Subur Indah Village, Katingan District, Kuala Central Kalimantan. The purpose of this study was to analyse the protein and calcium content of boiled white bird’s nest (Collacalia Fuchiphaga). Determination of protein content was carried out using the Kjeldahl method while for determination of calcium content using the permanganometric titration method. Based on the results with 3 repetitions each, the protein content was 21.8; 22.92 and 22.15% at 4 hours of boiling then 19.7; 18.1 and 19.05% at 8 hours of boiling. Meanwhile, the determination of the calcium content resulted in 201.5; 198.2 and 205.6 mg / 100 g calcium at 4 hours of boiling and 182.5; 178.8 and 175.6 mg / 100 g calcium. The conclusion in this study is that the longer it takes to boil a swallow's nest, the less protein and calcium content is obtained